Perancangan Interior Mall Pelayanan Publik di Surabaya Dengan Pendekatan Universal Design - Maria Silviana Dewi; Sherly de Yong; Hendy Mulyono (Intra, 2018)
Along with the era development, a lot of things that once was difficult becomes easier. The local government is developing a Public Service Mall to take care of all the stewardship of licensing letters and other things related to the government. However, this Public Service Mall is still lacking facilities for people with special needs even though the mall was developed in order to facilitate all Surabaya people without any exception. The design is expected to support the functioning of Public Service Mall as well as to support facilities for people with special needs to be able to perform their activities independently. Moreover, the design is also expected to make the disabled people feel comfortable to do their activities in the Public Service Mall.                The method used in this design is by performing field analysis and using design thinking method to analyze the problems, prototyping, until the implementation stage. The result from analysis to the implementation stage of the design was to make an innovation by adding an assistant corner to help people with special needs when doing activities in this Public Service Mall. The design of Public Service Mall can help disabled people, especially the people of Surabaya to do their activities independently, and not only helping the community at the moment but also in the future.